Implikasi Cacat Kehendak Perjanjian Waris terhadap Kepastian Hukum Sertipikat Tanah dan Upaya Preventif BPN Kabupaten Gresik - KAMILA FEBRIYANA (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Land registration aims to provide legal certainty, but land certificates can become controversial if the basis for issuing them, such as the Deed of Distribution of Inheritance Property (APHW), contains a flawed will. This study aims to analyze the legal implications of a flawed will in an inheritance distribution agreement on the legal certainty of land certificates, as well as legal protection for legitimate heirs. This study is a normative legal study with a statutory approach. The results show that inheritance distribution agreements containing elements of coercion, fraud, error, or abuse of circumstances can be canceled because they violate the legal requirements of the agreement as stipulated in Article 1320 of the Civil Code. As a result, the transfer of land rights and certificates issued based on these rights lose their legal binding force and can be canceled. Then, legal protection for legitimate heirs is realized through the principle of nemo plus juris in a system of negative publication with a positive tendency. As a preventive measure, the Gresik Regency Land Office (BPN) conducts thorough verification of the validity of legal and administrative data before processing land rights transfers.